When is a hydrophobic gate not a hydrophobic gate? - Seiferth, D; Biggin, PC; Tucker, SJ (Rockefeller University Press, 2022)
The flux of ions through a channel is most commonly regulated by changes that result in steric occlusion of its pore. However, ion permeation can also be prevented by formation of a desolvation barrier created by hydrophobic residues that line the pore. As a result of relatively minor structural changes, confined hydrophobic regions in channels may undergo transitions between wet and dry states to gate the pore closed without physical constriction of the permeation pathway. This concept is referred to as hydrophobic gating, and many examples of this process have been demonstrated. However, the term is also now being used in a much broader context that often deviates from its original meaning. In this Viewpoint, we explore the formal definition of a hydrophobic gate, discuss examples of this process compared with other gating mechanisms that simply exploit hydrophobic residues and/or lipids in steric closure of the pore, and describe the best practice for identification of a hydrophobic gate.